Adventures in Chinese realism : classic philosophy applied to contemporary issues - Harris, Eirik Lang; Schneider, Henrique (State University of New York Press, 2022)
"Relates Chinese Realism to contemporary political and ethical challenges, for example in international relations and the morality of the public sector"-- Provided by publisher.
Keywords: Han, Fei, -- -233 B.C. -- Han Feizi.; Han Feizi (Han, Fei); Legalism (Chinese philosophy); Realism.; Taoism.; Philosophy, Chinese -- To 221 B.C.; Political science -- Philosophy.; China -- Politics and government -- To 221 B.C.; Réalisme.; Taoïsme.; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; Chine -- Politique et gouvernement -- Jusqu'à 221 av. J.-C.; International Relations.; China.; Asia.; HISTORY.; Comparative.; LAW.; Eastern.; PHILOSOPHY.; Ethics & Moral Philosophy.; Political.; POLITICAL SCIENCE.; Philosophy, Chinese; Political science -- Philosophy; Politics and government; Realism; Taoism; China; To 221 B.C.